ANALISA PERBEDAAN KINERJA KEUANGAN (MARKET RATIO) PADA PERUSAHAAN PARTISIPAN INDONESIA SUSTAINABILITY REPORT AWARD (ISRA) 2009-2011 - Widyastuti, Widyastuti (Business Accounting Review, 2014)
The purpose of this research was to know the difference of financial performance on participant firms of Indonesia Sustainability Report Award (ISRA) 2009-2011. Market measurements used in this research were Price Earning Ratio and Market to Book Ratio. Firm performance data based on firmâs annual report from 2009-2011 and participating firm data from the Report of the Judges ISRA. The test used in research were independent t test, One Way ANOVA, and MANOVA test by using SPSS 19. The research sample were 30 companies participating in Indonesia Sustainability Report Award on 2009-2011 listed in Indonesia Stock Exchange. The result of the research showed that only Market to Book Ratio of participant of Indonesia Sustainability Reporting Award showed difference between manufacturing and service sectors. Meanwhile, there was no difference of PER and MBR of participating and size variable. This indicated that investors didnât know about ISRA so they didnât use the information available in this award.